Capacity guaranteed sleep mode algorithm for 5G femtocell tier - Christos Bouras; Georgios Diles; Konstantinos Nikolareas (International Symposium on Networks, Computers and Communications (ISNCC' 19) - Wireless and Mobile Networks, 2019)
The upcoming 5G networks require an advanced planning in terms of coordinating various mechanisms to achieve the highly expected performance growths that they pledge. This coordination becomes more challenging due to the increased density in urban environments of the deployment of small radius base stations, such as femtocells. In this paper we test our proposed mechanism for sleep mode power control in femtocell networks, over a widely used simulated traffic model, adjusted to our scenario. Our sleep mode strategy has been developed for femtocell clusters with the goal of reducing the number of operating femtocells without compromising the data rate performance of their subscribers. Our simulations reaffirm the benefits of our algorithm, especially the reduced number of operating femtocells and the increased offered capacity, when tested in realistic environments.